2017
DOI: 10.1152/ajpendo.00062.2017
|View full text |Cite
|
Sign up to set email alerts
|

Lipid droplet size and location in human skeletal muscle fibers are associated with insulin sensitivity

Abstract: In skeletal muscle, an accumulation of lipid droplets (LDs) in the subsarcolemmal space is associated with insulin resistance, but the underlying mechanism is not clear. We aimed to investigate how the size, number, and location of LDs are associated with insulin sensitivity and muscle fiber types and are regulated by aerobic training and treatment with an erythropoiesis-stimulating agent (ESA) in healthy young untrained men. LD analyses were performed by quantitative transmission electron microscopy, and insu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 44 publications
(58 reference statements)
7
47
0
Order By: Relevance
“…In type II fibers, IMCL content, LD size and number in the SS region correlated negatively with insulin sensitivity, suggesting that specifically SS LDs may somehow interfere with insulin sensitivity. This is in line with the negative association of specifically SS LD diameter and insulin sensitivity observed previously in healthy young men [26] . LDs in the SS region are in direct vicinity of cellular membrane, a site where LDs or bioactive LDs released from these droplets, can readily interfere with insulin signaling.…”
Section: Discussionsupporting
confidence: 92%
“…In type II fibers, IMCL content, LD size and number in the SS region correlated negatively with insulin sensitivity, suggesting that specifically SS LDs may somehow interfere with insulin sensitivity. This is in line with the negative association of specifically SS LD diameter and insulin sensitivity observed previously in healthy young men [26] . LDs in the SS region are in direct vicinity of cellular membrane, a site where LDs or bioactive LDs released from these droplets, can readily interfere with insulin signaling.…”
Section: Discussionsupporting
confidence: 92%
“…Increased IMTG content near the plasma membrane of muscle fibres has been associated with insulin resistance (Chee et al 2016) particularly if IMTG is stored in larger LDs (Nielsen et al 2017;Daemen et al 2018). Accumulation of IMTG close to the plasma membrane may be detrimental due to the close proximity to key components of the insulin signalling cascade.…”
Section: Discussionmentioning
confidence: 99%
“…The primary aim of this study was to test the hypothesis that in healthy individuals that have consumed a HFHC diet for 7 days there is an increase in IMTG stores and a reduction or no change in the concentration of lipid metabolites known to disrupt the insulin signalling cascade in insulin-resistant states. Fibre type and subcellular distribution of IMTG, as well as the size of LDs containing IMTG are all closely linked to insulin resistance (Chee et al 2016;Nielsen et al 2017;Daemen et al 2018). To detect nuanced changes in IMTG stores following a HFHC diet, we employed our previously validated microscopy techniques (Shepherd et al , 2013(Shepherd et al , 2017 to allow us to investigate changes in LD morphology and subcellular distribution on a fibre type-specific basis.…”
Section: Introductionmentioning
confidence: 99%
“…However, the association between intramyocellular lipid accumulation and insulin resistance is well-documented ( Phillips et al, 1996 ; Pan et al, 1997 ). Hence, it was suggested that LD size in the subsarcolemmal space has a major incidence on the onset of insulin resistance in humans ( Nielsen et al, 2017 ). Also, it was recently suggested that impaired insulin resistance would not occur in response to increased myocellular lipid contents but rather to larger LDs.…”
Section: Discussionmentioning
confidence: 99%